Bacterial resistance to vancomycin: Overproduction, purification, and characterization of VanC2 from Enterococcus casseliflavus as a d-Ala-d-Ser ligase - Park, Il-Seon (The National Academy of Sciences of the USA, 1997)
The VanC phenotype for clinical resistance of enterococci to vancomycin is exhibited by Enterococcus gallinarum and Enterococcus casseliflavus. Based on the detection of the cell precursor UDP-N-acetylmuramic acid pentapeptide intermediate terminating in d-Ala-d-Ser instead of d-Ala-d-Ala, it has been predicted that the VanC ligase would be a d-Ala-d-Ser rather than a d-Ala-d-Ala ligase. Overproduction of the E. casseliflavus ATCC 25788 vanC2 gene in Escherichia coli and its purification to homogeneity allowed demonstration of ATP-dependent d-Ala-d-Ser ligase activity. The k(cat)/K(m2) (K(m2) = K(m) for d-Ser or C-terminal d-Ala) ratio for d-Ala-d-Ser/d-Ala-d-Ala dipeptide formation is 270/0.69 for a 400-fold selection against d-Ala in the C-terminal position. VanC2 also has substantial d-Ala-d-Asn ligase activity (k(cat)/K(m2) = 74 mM(−1)min(−1)).